Adiabatic monoparametric autonomous motors enabled by self-induced nonconservative forces - Kurnosov, Arkady (2022)
Archetypal motors produce work when two slowly varying degrees of freedom (DOF) move around a closed loop of finite area in the parameter space. Here, instead, we propose a simple autonomous monoparametric optomechanical engine that utilizes nonlinearities to turn a constant energy current into a nonconservative mechanical force. The latter self-sustains the periodic motion of a mechanical DOF whose frequency is orders of magnitude smaller than the photonic DOF. We identify conditions under which the maximum extracted mechanical power is invariant and show self-induced robustness of the power production against imperfections and driving noise.